If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 5i = 7 + 2i Solving 5 + 5i = 7 + 2i Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-2i' to each side of the equation. 5 + 5i + -2i = 7 + 2i + -2i Combine like terms: 5i + -2i = 3i 5 + 3i = 7 + 2i + -2i Combine like terms: 2i + -2i = 0 5 + 3i = 7 + 0 5 + 3i = 7 Add '-5' to each side of the equation. 5 + -5 + 3i = 7 + -5 Combine like terms: 5 + -5 = 0 0 + 3i = 7 + -5 3i = 7 + -5 Combine like terms: 7 + -5 = 2 3i = 2 Divide each side by '3'. i = 0.6666666667 Simplifying i = 0.6666666667
| 7y+2y-8y=18 | | 4G+7=5G-1+G | | 59-(3x-5)=5x | | 5n+7+n=(2n+1)+3n-2+n | | 13-2(3x-7)=9 | | 10x-4x+124=10x+64 | | 5+r=r+4+1 | | 9h-7h=10 | | 3x-4=-6x+23 | | 5+5h=7+2h | | -4+1-4= | | 15n+65=35 | | 8+40x+5-5x=13 | | 9x-5=4x-8 | | 15n^2+34n+15=0 | | -4.45-2=5.5s-4.2 | | x=y^2-6y+13 | | 9x-5=-4x-8 | | 9-11x-6-3x=5 | | x=y^2-6x+13 | | 6u-2u=16 | | P*4-13= | | 123=8.50x+55 | | 3(2x+2)+8=44 | | 79-x+96-2x=180 | | 5X-1=7X+7 | | -3p+8=-48+12 | | 19u-17u=4 | | -1+-2=7X+7 | | 7x-9=7(x-9) | | 5p*3+4-4*3-13= | | 79-x+95-2x=90 |